2015
DOI: 10.5194/acp-15-5359-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mercury vapor air–surface exchange measured by collocated micrometeorological and enclosure methods – Part II: Bias and uncertainty analysis

Abstract: Abstract. Dynamic flux chambers (DFCs) and micrometeorological (MM) methods are extensively deployed for gauging air-surface Hg 0 gas exchange. However, a systematic evaluation of the precision of the contemporary Hg 0 flux quantification methods is not available. In this study, the uncertainty in Hg 0 flux measured by the relaxed eddy accumulation (REA) method, the aerodynamic gradient method (AGM), the modified Bowen ratio (MBR) method, as well as DFC of traditional (TDFC) and novel (NDFC) designs, are asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 64 publications
3
38
0
2
Order By: Relevance
“…The bimodal pattern of GEM fluxes has been observed previously by others (e.g. Fritsche et al, 2008b;Bash and Miller, 2008;Zhu et al, 2015) and attributed to co-deposition of mercury with dew overnight, with subsequent re-volatilisation of GEM as the dew is evaporated from the surface. The linear correlation of GEM fluxes with latent heat fluxes in this study similarly provides evidence for this explanation of the bimodal GEM flux pattern.…”
Section: Environmental Correlatessupporting
confidence: 50%
See 1 more Smart Citation
“…The bimodal pattern of GEM fluxes has been observed previously by others (e.g. Fritsche et al, 2008b;Bash and Miller, 2008;Zhu et al, 2015) and attributed to co-deposition of mercury with dew overnight, with subsequent re-volatilisation of GEM as the dew is evaporated from the surface. The linear correlation of GEM fluxes with latent heat fluxes in this study similarly provides evidence for this explanation of the bimodal GEM flux pattern.…”
Section: Environmental Correlatessupporting
confidence: 50%
“…The low linear correlation between GEM flux and soil temperature compared to scalar fluxes of heat may suggest that turbulent atmospheric processes (quasi-laminar and turbulent diffusion), rather than insoil processes, represent the larger influence on GEM fluxes. Zhu et al (2015) found stronger relationships between aerodynamic variables and GEM fluxes when measured by micrometeorological methods than when measured with flux chambers, suggesting the choice of measurement may influence these relationships. Edwards and Howard (2013) however similarly observed stronger relationships with atmospheric variables and GEM fluxes measured using dynamic flux chambers over bare background THg soil.…”
Section: Environmental Correlatesmentioning
confidence: 92%
“…There has not been a standardized protocol for any of the techniques (e.g., instrumentation set-up, operation parameters) (Gustin, 2011;Zhu et al, 2015b). Recent collocated measurements and uncertainties analysis emphasized the importance of method standardization and processing of field data acquired by the measurement systems (Fritsche et al, 2008b;Converse et al, 2010;Zhu et al, 2015a). Application of the appropriate flux measurement technique depends on the scalar detection accuracy, sensor response frequency and level of automation (Sutton et al, 2007).…”
Section: Advances In Hg 0 Flux Quantification Methodsmentioning
confidence: 99%
“…2). Direct measurement of Hg 0 flux from the background surfaces is difficult due to small vertical Hg 0 concentration gradients (therefore low flux) (Zhu et al, 2015a). Since the first application of a stainless steel dynamic flux chamber for Hg 0 flux measurements over background lakes and soils in the 1980s (Schroeder et al, 1989;Xiao et al, 1991), significant advancements in the experimental approaches (e.g., dynamic flux chambers, micrometeorological methods, the Hg 0 / 222 Rn flux ratio, enriched isotope tracer methods, the open-path laser optical spectroscopic method and the Hg 0 / CO ratio) have been made (Sommar et al, 2013a).…”
Section: W Zhu Et Al: Global Observations and Modeling Of Mercury Fmentioning
confidence: 99%
See 1 more Smart Citation